Description of Coffee Consumption Patterns at The Productive Age in The Times Covid-19 Pandemic - Dwita Meylina Nur Aisyah; Farah Nurul Basma; Hanifah Sekar Wulandari; Munaya Fauziah (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
Background Coffee is one of the drinks that are often consumed by the people of Indonesia. In Indonesia, the age of coffee connoisseurs is almost irrespective of age ranging from teenagers to adults and even seniors, so there are countless. The tradition of drinking coffee, especially in the morning, is a habit of people every day. Based on the results of a survey conducted by Maspul in Kurniawan, et al (2020) it was found that during the COVID-19 pandemic, consumers were more likely to consume coffee drinks in the form of sachets which did not take long to serve. Furthermore, he stated that during the COVID-19 pandemic there was a tendency to increase consumption of ready-to-drink instant coffee such as cold coffee beverages, ready-to-drink coffee, and specialty instant coffee. Objective This study aims to describe the pattern of coffee consumption at productive age during the COVID-19 pandemic in 2021. Design descriptive research method with a qualitative approach to design cross-sectional. The sample in this study was three (3) female students and directed the research target to an effort to find a theory from the base (grand theory) which aims to understand the phenomena experienced by the research subjects. Result Characteristics of respondents The research was conducted with 3 respondents in the productive age group who will describe or construct in-depth interviews with research subjects so that they can provide a clear picture of coffee consumption patterns in productive ages during the COVID-19 pandemic.